Integrated assessment of biomarker responses in algae Chlorella sorokiniana exposed to copper and cadmium - titi hayati rahayu; ANDHIKA PUSPITO NUGROHO (Society for Indonesian Biodiversity, 2020)
Abstract. Rahayu TH, Nugroho AP. 2020. Integrated assessment of biomarker responses in algae Chlorella sorokiniana exposed to copper and cadmium. Biodiversitas 21: 3569-3575. Microalgae Chorella as a major producer in aquatic ecosystems has high probability ofth being exposed to metal pollutants. Metal exposure to algae can induce the formation of reactive oxygen species (ROS), leading to oxidative stress states. ROS trigger the responses of biomarkers of antioxidative enzymes, including superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX). This study aims to develop an integrated biomarker response index and star plot for interpretation of the antioxidative enzyme responses in Chlorella sorokiniana. The microalgae was exposed to three concentrations of copper (Cu) and cadmium (Cd) for 48 h, respectively. The results showed that exposure to Cu and Cd caused an increase of protein content and activities of SOD and APX. Analysis of integrated biomarker response (IBR) showed a decrease in the value of IBR along with an increase in cadmium concentration but no similar pattern found in copper. The multiple factor analysis (MFA) approach showed that exposure to Cu 0.3 ?mol L-1 for 48 h had high score of protein content and SOD activity in the first dimension. For the second dimension, exposure to Cu 1.6 µmol L-1 for 6 h had high score of APX and SOD activity.